การทำน้ำส้มเข้มข้นด้วยวิธีออสโมซิสแบบย้อนกลับ - ธนกร ศิริอังคณา (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
Nowadays, heat treatment is often used to concentrate fruit juice. Many studies have shown that the heat evaporation of fruit juice has a detrimental effect on its chemical and physical properties. The aim of this work is to study the possibility of using reverse osmosis in concentrating fruit juice without using heat. Orange juice was used as a model fruit juice. The reverse osmosis process in this work was a recirculation filter system. Cross-flow filtration was used, and the water orange juice was filtered into through a tubular membrane module with a diameter of 1.15 cm (a retentate flow cross-sectional area is of 1.04 cm²). Membrane was made of Acetylcellulose acetylcellulose. The filtration area was 110 cm², the filtration pressure was 2.5 MPa, the retention velocity through the membrane was 1.6 m/s, and the filtration was performed at a temperature below 30 °C. The filtration rate of the filtrate and percent rejection were monitored for 180 minutes, and It was found that the filtration rate decreased rapidly at first, then steadily decreased. After 150- 180 minutes of filtration, the filtering rate was 0.0009 mm/s. The percent rejection was 91-95% at the beginning, increased with filtration time and reached 96-97% at 90 minutes). It can be seen that this process can concentrate orange juice. After filtration, the total phenolic content decreased to 56.3%, while the antioxidant activity of concentrated fruit juices determined by DPPH and FRAP methods decreased to 33.0% and 49.7% respectively, as compared to the pre-filtered one. Furthermore, removing the gel layer that was supposed to formed on the membrane surface during filtration, which is was considered to be the main reason of the reduction in filtration rate. Therefore, after the filter was set for a duration of filtration was conducted for 60 minutes, the filter pressure was reduced to 0 MPa while the velocity of the retentate flowing through the membrane was increased to 1.8 m/s for 5 minutes, It was found that the filtration rate was increased by 35.4% as compared to the final filtration rate before the removal of the gel layer on the membrane surface. The study revealed that the filtration efficiency can be extended by reverse osmosis process.